2011
DOI: 10.1242/jcs.081422
|View full text |Cite
|
Sign up to set email alerts
|

A central multifunctional role of integrin-linked kinase at muscle attachment sites

Abstract: SummaryIntegrin-linked kinase (ILK) is an essential component of a multiprotein complex that links actin to the plasma membrane. Here, we have used a genetic approach to examine the molecular interactions that are essential for the assembly of this ILK-containing complex at Drosophila muscle attachment sites (MASs). We show that, downstream of integrins, talin plays a decisive role in the recruitment of three proteins: ILK, PINCH and paxillin. The accumulation of ILK at MASs appears to follow an amplification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
2
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 60 publications
4
38
2
4
Order By: Relevance
“…This indicates that the PINCH C-terminal tail also participates in localization, even in the context of normal binding to ILK (Xu et al, 2005). A recent study, that is complementary to this report, has probed how various ILK deletion mutants affect protein assembly at muscle attachment sites (Zervas et al, 2011). This work demonstrates that expression and proper localization of the ANKR domain of ILK in an ilk null mutant is insufficient to localize PINCH despite the capacity of PINCH to bind this portion of ILK (Zervas et al, 2011).…”
Section: Requirements For Pinch and Ilk Localization At Muscle Attachsupporting
confidence: 54%
See 4 more Smart Citations
“…This indicates that the PINCH C-terminal tail also participates in localization, even in the context of normal binding to ILK (Xu et al, 2005). A recent study, that is complementary to this report, has probed how various ILK deletion mutants affect protein assembly at muscle attachment sites (Zervas et al, 2011). This work demonstrates that expression and proper localization of the ANKR domain of ILK in an ilk null mutant is insufficient to localize PINCH despite the capacity of PINCH to bind this portion of ILK (Zervas et al, 2011).…”
Section: Requirements For Pinch and Ilk Localization At Muscle Attachsupporting
confidence: 54%
“…In Drosophila, ilk null mutational analyses have shown that ILK is required for the appropriate targeting of PINCH to integrin-rich adhesion sites (Zervas et al, 2011). In contrast, we have found that PINCH Q38A -Flag, which lacks the ability to bind ILK, assembles properly at muscle attachment sites, supporting the retention of cellular and muscle architecture, as well as viability of the organism.…”
Section: Requirements For Pinch and Ilk Localization At Muscle Attachmentioning
confidence: 59%
See 3 more Smart Citations